Dual Gold‐Catalyzed Three‐Component Reaction: Efficient Synthesis of Indene‐Fused Esters, Acids, and Lactones through Gold Vinylidene Intermediates. Issue 11 (24th March 2017) - Yu, Congjun; Ma, Xiaodong; Chen, Bin; Tang, Bencan; Paton, Robert S.; Zhang, Guozhu
Abstract : A dual gold(I)‐catalyzed three‐component reaction was developed to prepare indene‐fused carboxylic acid derivatives from diynes, alcohols, and pyridine N ‐oxides in both inter‐ and intramolecular fashions. The pyridine N ‐oxides were found to exhibit distinct selectivity unlike the α‐oxo gold carbene intermediates in the well‐developed gold‐catalyzed oxidative functionalization of alkynes. Experimental studies and DFT calculations support double nucleophilic substitution of a gold vinylidene intermediate. Abstract : A dual gold(I)‐catalyzed three‐component reaction is developed to prepare indene‐fused carboxylic acid derivatives from diynes, alcohols, and pyridine N ‐oxides in both inter‐ and intramolecular fashions. Pyridine N ‐oxides exhibit unique reactivity and selectivity to oxidize the gold vinylidene. Experimental studies and DFT calculations support ketene formation as the key step.